2007
DOI: 10.1111/j.1467-8691.2007.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Leader Self‐Reported Emotional Intelligence and Perceived Employee Creativity: An Exploratory Study

Abstract: This research studies the relationship between six dimensions of leaders' emotional intelligence and two dimensions of employee creativity. A sample of 138 managers from 66 organizations reported on their own emotional intelligence and the creativity of their teams. Our results point out two main findings: (a) leaders' emotional intelligence explains significant variance of both creativity dimensions; (b) emotional intelligence dimensions with higher predictive power are self-control against criticism and empa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 60 publications
2
151
1
7
Order By: Relevance
“…Leaders should be emotionally intelligent to stimulate the creativity of their employees. Also, Vesterinen et al emphasized that, the nurse manager's ability to reflect on their own behaviour makes it easier to regulate and estimate their leadership practice with different employees in different situations [39]. However, it is important to remember that there are situations in which nurse managers have to make difficult decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders should be emotionally intelligent to stimulate the creativity of their employees. Also, Vesterinen et al emphasized that, the nurse manager's ability to reflect on their own behaviour makes it easier to regulate and estimate their leadership practice with different employees in different situations [39]. However, it is important to remember that there are situations in which nurse managers have to make difficult decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Rego et al highlighted that, differences in work units, employees and situations, make no only correct leadership style and behaviours; the same result can be achieved in many ways [39]. Leaders should be emotionally intelligent to stimulate the creativity of their employees.…”
Section: Discussionmentioning
confidence: 99%
“…Barczak, Lassak, and Mulki (2010) concluded that emotional intelligence has a positive influence on trust, which in turn enhances collaborative culture, which increases team creativity. Castro and Jorge de Sousa (2012) reported that leaders' emotional intelligence was positively associated with employees' creativity, and Rego et al (2007) suggested that leaders' emotional intelligence stimulates creativity in their teams. Even though SI is different from emotional intelligence, there are some overlaps between these two constructs.…”
Section: Creative Performancementioning
confidence: 99%
“…Luthans, Youssef, and Avolio [47] later proposed supplementary PsyCaps related to wisdom, such as gratitude, forgiveness, spirituality, courage, and emotional intelligence (EI). For this article, PsyCap-EI is selected as the fifth resource, defined as the ability to manage one's emotions and perceive emotions in others [55].…”
Section: Components Of Psychological Capitalmentioning
confidence: 99%